Strengthening the Euro Area the role of national structural reforms in enhancing resilience - Aiyar, Shekhar (IMF staff discussion note ;, 2019)
The SDN will focus mostly on EA countries but also touch on other AEs for comparison purposes. The SDN will make several original contributions in each of the areas above based on new DSGE-model-based analysis, cross-country panel regressions, and individual-level (firm- or household-level) empirical work where appropriate.